Impact of Hormonal Therapy on Endometriosis-Associated Pain and Fertility - Munazza Yousaf, Zareena Begum, Abeer, Fatima Usama, Shermeen Kousar, Naureen Ghani (Pakistan Journal of Medical & Health Sciences, 2025)
Introduction: Endometriosis is a chronic gynecological condition associated with severe pelvic pain and infertility. Hormonal therapy, including GnRH agonists, combined oral contraceptives (COCs), and progestins, is widely used for symptom management. However, the comparative efficacy of these treatments in pain reduction and fertility outcomes remains unclear. This study aimed to evaluate the impact of hormonal therapy on endometriosis-associated pain and fertility. Methodology: This prospective cohort research was carried out from February 2023 to July 2023, at the department of Gynaecology and Obstetrics, Saidu Group of Teaching Hospitals, Swat and MMC General Hospital, Peshawar. Three treatment groups were created from 98 women with endometriosis diagnoses: progestins (n=33), COCs (n=32), and GnRH agonists (n=33). The Visual Analog Scale (VAS) was used to measure pain severity both at baseline and one year later. Ovulation and pregnancy rates were among the fertility outcomes that were documented. ANOVA, chi-square tests, and paired t-tests were used in the statistical analysis; a p-value of less than 0.05 was deemed statistically significant. Results: GnRH agonists showed the greatest pain reduction (VAS: 8.0 → 1.9, p < 0.001) but had the highest side effects and lowest adherence (69.7%). COCs and progestins demonstrated moderate pain relief with better tolerability (VAS reduction: 7.9 → 3.2 and 7.8 → 2.9, respectively). Ovulation and pregnancy rates were highest in the GnRH group (69.2% and 53.8%) but were not statistically significant (p > 0.05). Conclusion: Hormonal therapy effectively reduces endometriosis-associated pain, with GnRH agonists providing the best relief but lower adherence. Fertility outcomes showed improvement but lacked statistical significance. Further research is needed to assess long-term effects and optimize treatment strategies. Keywords: Endometriosis, Hormonal Therapy, GnRH Agonists, Pain Management, Fertility, Combined Oral Contraceptives, Progestins